Real‐life self‐assessment of pruritus relief with a combination of calcipotriol/betamethasone dipropionate foam in patients with plaque psoriasis - Laurent Misery; Jessica Gonnet; Nadine Mackenzie; Nathalie Beneton; Bruno Halioua (Wiley, 2022)
Abstract Objectives Psoriasis‐related pruritus is a frequent and underestimated symptom with a strong impact on quality of life, psychological condition and sleep. Our main objective was to document, in real‐life clinical practice, the perception of pruritus and the efficacy of a 4‐week topical treatment with a fixed‐dose combination of calcipotriol/betamethasone dipropionate (Cal/BD) foam on psoriasis‐related moderate‐to‐severe pruritus. Methods This was an exploratory prospective observational study in psoriasis patients with a pruritus visual analogic scale (VAS) score ≥ 3/10 cm. The primary endpoint was the proportion of responder patients defined as the self‐assessed improvement from baseline of pruritus of at least 2 VAS score points 48 h after the first topical administration. The quality of sleep was assessed on VAS and the quality of life was assessed using the Dermatology Life Quality Index (DLQI) on Day 28. Results A total of 81 patients were included by 34 dermatologists and 40 self‐questionnaires were evaluable for efficacy on Day 28. At inclusion, pruritus was self‐assessed as severe by 60.8% of patients, whereas physicians reported severe pruritus in 16.9% of patients. A proportion of 91.4% (95% confidence interval: 82-100) of patients were responders to pruritus relief 48 h after the first Cal/BD application. Relevant improvements in quality of sleep after 24 h (+2.9 ± 3.0) and in quality of life after 28 days (−9.0 ± 6.8) were reported. Conclusion This exploratory study provides further evidence that pruritus is an underestimated symptom, and it confirms the usefulness of the fixed‐dose combination of Cal/DB foam in relieving moderate‐to‐severe pruritus and improving the quality of life and sleep in patients with plaque psoriasis.